Da dinâmica oscilatória entre regiões envolvidas no processamento de detecção de novidades - Santos, Calline Palma dos (2020)
Memory is one of the cognitive functions with proven relevance for the development of skills necessary for the adaptability of species, which are inherent to their survival. The objective proposed here was to analyze the theta-gamma cross-frequency coupling during an object recognition task. The main objective was to verify the existence of a specific electrophysiological signature during object exploration, both in the circumstance of novelty (encoding) and evocation. More specifically, differences between phase-amplitude coupling between theta and multiple faster frequencies in both situations were investigated. The research was carried out using the hc-25 dataset made available by Michaël Zugaro: "Recordings and timed stimulation of rat dorsal hippocampal area CA1 and medial prefrontal cortex during behavior and sleep (available at http://crcns.org/data-sets/hc/hc-25/). The methodological procedures consisted in the creation of customized analysis routines, whose functions enabled the extraction of properties from the recorded signal. The properties investigated provided the establishment of the study and interpretation of the characteristics of rhythmic functioning of the frequency bands extracted from the method of empirical mode decomposition (EMD) for the extraction of raw neural signals of Local Field Potentials in various frequency bands. In this way, individual theta cycles (Theta-Nested Spectral Components- tSCs) captured during periods of exploratory behavior activity and object recognition were characterized. When comparing the average strength of the theta cycles obtained during object exploration and active locomotion, we found that only the strength of the gamma-related theta is significantly higher, even when controlling for the speed of the animal. Next, force values were compared between cycles from object exploration (by definition when the animal is stationary or at low speed) and cycles during slow speeds (<10 cm/s). We found that, again, only tSC4 has higher mean force during object exploration, while the other tSCs are not significantly different. The working hypothesis admitted here is that if tSC4 is involved with encoding, we would expect to see a decrease in its strength during the test; more so, we would expect to see a decrease during exploration of the "old" object compared to the "new" (displaced) object. However, it was seen that no differences were detected for all tSCs. Therefore, due to research limitations and the need for adaptations related to the method of data collection presented, more detailed studies with larger sample size will be conducted so that the study is amenable to greater generalizations.